The Caudal Urophysis of Carasobarbus luteus and Capoeta trutta caught from river Tigris passing through Mosul city - Al-Shatter, Nabela M.S.; F.Rahemo, ZohairI (Sulaimani Journal for Pure and Applied Sciences, 2014)
Two freshwater fish models were selected, to study their caudal neurosecretory system, caught in river Tigris passing through Neinava province. A total of 45 Carasobarbus luteus and 32 of , Capoeta trutta were examined to study their caudal neurosecretory system of gross morphological and histological aspects. The caudal spinal cord in B. luteus is a lobulted organ, possesses (3-5) lobules which are oval or ovoid, each lobule measures (450-675) μm and average diameter is (270) μm, situated in postero-ventral part of the spinal cord in the caudal region at the level of the last 5th vertebrate, while spinal cord in C. trutta lacks these lobules. The caudal spinal cord posseses three types of neurosecretory cells which appeared, after staining by three different stains. These cells are situated at ventro- and ventro-lateral region of spinal cord with respect to the central canal. These cells can be classified into three types, small, median, and large cells.Noteworthy, Dahlgren cells are associated with blood capillaries and it is easy to trace these cells with bulbous axons rich in secretary materials as a large amount of neurosecretory material deposited in them. Furthermore, neurosecretory material were deposited in the ventral part of the spinal cord which are known as Herring bodies, and blood vessels were observed near them, some axons of Dahlgren cells seen directed toward the blood capillaries
Keywords: fishes; urophysis; histology